2006
DOI: 10.1007/s00276-005-0073-9
|View full text |Cite
|
Sign up to set email alerts
|

Risky anatomic variations of sphenoid sinus for surgery

Abstract: We searched for the surgically risky anatomic variations of sphenoid sinus and aimed to compare axial and coronal tomography in detection of these variations. Fifty-six paranasal tomography images (112 sides) were evaluated for coronal, axial and both coronal and axial images. Tomographic findings including bony septum extending to optic canal or internal carotid artery; protrusions and dehiscences of the walls of internal carotid artery, optic nerve, maxillary nerve and vidian nerve; extreme medial course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
125
6
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(158 citation statements)
references
References 27 publications
23
125
6
4
Order By: Relevance
“…The opticocarotid recess is presumed to concur with ipsilateral optic nerve protrusion into the sphenoid sinus 8 . Sirikci et al 1 , Ünal et al 4 and Hewaidi et al 8 reported a significant relationship between protrusion of the ON into SS and the pneumatization of ACP. We observed 23.5 % patients on the right side and 14.7 % patients on the left side with both pneumatization of ACP and protrusion of ON.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The opticocarotid recess is presumed to concur with ipsilateral optic nerve protrusion into the sphenoid sinus 8 . Sirikci et al 1 , Ünal et al 4 and Hewaidi et al 8 reported a significant relationship between protrusion of the ON into SS and the pneumatization of ACP. We observed 23.5 % patients on the right side and 14.7 % patients on the left side with both pneumatization of ACP and protrusion of ON.…”
Section: Discussionmentioning
confidence: 99%
“…Protrusion of optic nerve and bony dehiscence of the wall of optic nerve was evaluated according to the criteria of Sirikci et al 1 and Ünal et al 4 . In coronal section, protrusion was defined as the presence of more than half the circumference of the concerned structures into the sinus cavity with or without defects in their bony margins.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, the presence of the ICA and ON protrusions was identified and assessed on the axial plane according to Unal's method [6]. Briefly, the protrusion of the ICA was determined as finding for placement of ICA with 50% of its diameter in SS and obvious or light protrusions was determined as finding for placement of ICA with more than 50% or 10% -50% of its diameter.…”
Section: Methodsmentioning
confidence: 99%
“…However, the protrusions don't appear in all cases. The prevalence of the protrusions is quite variable, which may affect the success of transsphenoidal endoscopic surgery [6,[8][9][10][11][12][13]. The prevalence of protrusion of ICA is not conclusive, ranging from 5.2% [14] -32.8% [15], 48.5% [16] and 67.7% [8], depending on the degree of individual pneumatization and the definition used in each study.…”
Section: The Relationship Between Ss Volume and Transsphenoidal Surgimentioning
confidence: 99%
See 1 more Smart Citation